Effects of Mixed Yeast Fermentation on Volatile Compounds Composition of Arabica Coffee Beans - Utami, Whitney Jovanka; Suroto, Dian Anggraini; Setyabudi, Francis Maria Constance Sigit; Davinia, Alyssa Putri; Ratri, Dyah Sekar Purnama (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2025)
Coffee is part of the most highly valued agricultural commodities, and fermentation is an alternative method to enhance the quality of coffee beans. Therefore, this study aimed to assess the effects of Wickerhamomyces anomalus and Kluyveromyces lactis on the fermentation of Arabica coffee, particularly the contributions to volatile compounds formed in roasted beans. The fermentation process was further carried out by incorporating W. anomalus and K. lactis for 48 hours at room temperature. The results showed that fermenting for 12 hours with mixed yeast inoculation significantly increased the total yeast count and volatile compounds. Additionally, the fermentation of Arabica coffee with mixed yeast inoculation at a 1:1 ratio produced the highest total titratable acidity and yeast count. The release of volatile compounds varied based on the activity of the microorganisms with the highest concentrations of naphthalene, α-himachalene, toluene 2, 4-diamine, and 3-pentanol detected in the samples. These results suggested that fermenting Arabica coffee with W. anomalus and K. lactis not only enhanced bean quality but also held promise for industrial application.